Novel Intrinsic Self‐Healing Poly‐Silicone‐Urea with Super‐Low Ice Adhesion Strength. Issue 22 (22nd March 2022) - Chen, Jun; Luo, Zhenyang; An, Rong; Marklund, Pär; Björling, Marcus; Shi, Yijun
Abstract: Accumulation of snow and ice often causes problems and even dangerous situations for both industry and the general population. Passive de‐icing technologies, e.g., hydrophobic, liquid‐infused bionic surfaces, have attracted more and more attention compared with active de‐icing technologies, e.g., electric heating, hot air heating, due to the passive de‐icing technology's lower energy consumption and sustainability footprint. Using passive de‐icing coatings seems to be one of the most promising solutions. However, the previously reported de‐icing coatings suffer from high ice adhesion strength or short service life caused by wear. An intrinsic self‐healing material based on poly‐silicone‐urea is developed in this work to address these problems. The material is prepared by introducing dynamic disulfide bonds into the hard phase of the polymer. Experimental results indicate that this poly‐silicone‐urea has a self‐healing efficiency of close to 99%. More interestingly, it is found that the coating prepared from this poly‐silicone‐urea has a super low ice adhesion force, only 7 ± 1 kPa, which is almost the lowest value compared with previous intrinsic self‐healing de‐/anti‐icing reports. This material can maintain low ice adhesion strength after healing. This intrinsic self‐healing poly‐silicone‐urea can meet several practical applications, opening the door for future sustainable anti‐/de‐icing technologies. Abstract : A high self‐healing efficiency poly‐silicone‐urea is successfully synthesized by introducing the dynamic diaminodiphenyl disulfide group into the bis(3‐aminopropyl)‐terminated polydimethylsiloxane through isophorone diisocyanate. It is found that poly‐silicone‐urea has a super low ice adhesion force of 7 ± 1 kPa, which can maintain well after healing.